2008
DOI: 10.1021/ja8030533
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Ten-Amino Acid Protein

Abstract: Abstract:What is the smallest protein? This is actually not such a simple question to answer, because there is no established consensus among scientists as to the definition of a protein. We describe here a designed molecule consisting of only 10 amino acids. Despite its small size, its essential characteristics, revealed by its crystal structure, solution structure, thermal stability, free energy surface, and folding pathway network, are consistent with the properties of natural proteins. The existence of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
326
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(348 citation statements)
references
References 22 publications
19
326
2
1
Order By: Relevance
“…The advantage of studying chignolin is that its experimental structure is known (30) and it has been simulated for 100 μs using a special purpose machine (1), in addition to many other simulation studies (e.g., refs. [31][32][33], which provides us with good reference data.…”
Section: Algorithmmentioning
confidence: 99%
“…The advantage of studying chignolin is that its experimental structure is known (30) and it has been simulated for 100 μs using a special purpose machine (1), in addition to many other simulation studies (e.g., refs. [31][32][33], which provides us with good reference data.…”
Section: Algorithmmentioning
confidence: 99%
“…Honda et al (2008) obtained the crystal structure of a b-hairpin miniature protein, termed CLN025, which is a synthetic molecule consisting of 10 naturally occurring amino acids. The linear sequence of amino acids of CLN025 is Tyr1-Tyr2-Asp3-Pro4-Glu5-Thr6-Gly7-Thr8-Trp9-Tyr10 (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous experiment, Honda et al 39 have studied the NMR spectra of CLN025 in solution and have identified the hydrogen bonds observed in the NMR structures. In Table I, we evaluated the conformational sampling efficiency of the hybrid ICMD method by calculating the percentage of the snapshots in the simulations that have the hydrogen bond distances observed in the NMR structures within a standard deviation of the mean distance reported.…”
Section: Resultsmentioning
confidence: 99%
“…In this section, we apply the hybrid ICMD method to simulate a ten amino acid peptide CLN025 (Figure 11) for which there is an ensemble of NMR structures available. 39 Additionally, there are NMR data on the possible hydrogen bonds present in this system. We compared the conformation sampling thus obtained in FIXMAN and hybrid ICMD simulations to experimental data obtained from NMR studies as well as to the conformational sampling in FLEXIBLE simulations.…”
Section: Application Of Hybrid Icmd To Longer Peptide Chainsmentioning
confidence: 99%